2015
DOI: 10.1007/s12020-015-0770-z
|View full text |Cite
|
Sign up to set email alerts
|

Associations between two single-nucleotide polymorphisms (rs1801278 and rs2943641) of insulin receptor substrate 1 gene and type 2 diabetes susceptibility: a meta-analysis

Abstract: The objective of the study is to assess the association between rs1801278 and rs2943641 of insulin receptor substrate 1 gene (IRS1) and the susceptibility to type 2 diabetes. A literature search strategy was conducted to identify all references lists of relevant studies. The fixed or random effect model was used to calculate the pooled ORs on the basis of heterogeneity. Further analyses were performed to explore the sources of heterogeneity by sensitivity analysis, meta-regression analysis, and subgroup analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…From developed countries, a limited number of studies related to IRS1 and IRS2 gene polymorphisms focused on T2DM, OSA and NAFLD separately, but no study has been investigated the polymorphism in patients with OSA and NAFLD both. Li et al [27] have shown that IRS1 gene plays an important role in T2DM risk, especially in Asian. It also indicates that IRS1 gene polymorphism is associated with T2DM risk in Caucasian.…”
Section: Discussionmentioning
confidence: 99%
“…From developed countries, a limited number of studies related to IRS1 and IRS2 gene polymorphisms focused on T2DM, OSA and NAFLD separately, but no study has been investigated the polymorphism in patients with OSA and NAFLD both. Li et al [27] have shown that IRS1 gene plays an important role in T2DM risk, especially in Asian. It also indicates that IRS1 gene polymorphism is associated with T2DM risk in Caucasian.…”
Section: Discussionmentioning
confidence: 99%
“…So far, different studies have shown that multiple risk genes play a critical role in the biological functions of insulin, include secretion, interaction with its receptor and insulin intracellular signaling. One of these genes is Insulin receptor substrate-1 (IRS-1) which is known as a central molecule in insulin signaling (13). IRS-1, as a linker protein between the insulin receptor and downstream molecules in different signaling pathways, mediates the metabolic and growthpromoting effects of insulin in target tissues (23).…”
Section: Discussionmentioning
confidence: 99%
“…GWA studies recognized FTO rs2943641 upregulation is associated with IR and risk of T2DM. [48]. In acute hyperglycemia and the estimation of insulin opposition in normal individual polymorphism (G>A) of IRS1 play an essential role in identifying IR in T2DM.…”
Section: Slc30a8 (Solute Carrier Family 30 Member 8)mentioning
confidence: 99%